2021
DOI: 10.1111/jfpe.13709
|View full text |Cite
|
Sign up to set email alerts
|

Comparative extraction of bromelain and bioactive peptides from pineapple byproducts by ultrasonic‐ and microwave‐assisted extractions

Abstract: Ultrasonic‐assisted extraction (UAE) and microwave‐assisted extraction (MAE) were used for the extraction of bioactive peptides from pineapple byproducts. Independent extraction parameters for UAE were ultrasonic amplitude (60–100%), extraction time (10–30 min), and solvent to material ratio (20–40 mL/g), whereas for MAE independent variables were microwave power (100–300 W), irradiation time (5–15 min), and feed to solvent ratio (1:8–1:12 g/mL). The optimized extraction conditions were 99.96%, 26.83 min, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 53 publications
0
12
1
1
Order By: Relevance
“…There is an increasing interest in producing bioactive peptides through the use of novel technologies such as HHP, ultrasounds, pulsed electric field, microwave and subcritical water hydrolysis. These technologies are in general used to increase the extraction yield and obtain a higher degree of hydrolysis (DH) in the production of bioactive peptides by enhancing the enzymatic hydrolysis, facilitating the release and recovery of peptides [18,19]. The use of such novel technologies has the additional advantages of being environmentally friendly, innovative and sustainable [20].…”
Section: Novel Technologies To Improve Enzymeassisted Hydrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…There is an increasing interest in producing bioactive peptides through the use of novel technologies such as HHP, ultrasounds, pulsed electric field, microwave and subcritical water hydrolysis. These technologies are in general used to increase the extraction yield and obtain a higher degree of hydrolysis (DH) in the production of bioactive peptides by enhancing the enzymatic hydrolysis, facilitating the release and recovery of peptides [18,19]. The use of such novel technologies has the additional advantages of being environmentally friendly, innovative and sustainable [20].…”
Section: Novel Technologies To Improve Enzymeassisted Hydrolysismentioning
confidence: 99%
“…The efficiency of ultrasound and microwave-assisted extraction was assayed for the extraction of bioactive peptides from pineapple by-products and both types of extraction were compared. The results showed that ultrasound-assisted extraction gave higher yield of peptides and proteolytic activity as a consequence of the lower temperature, especially if thermolabile substances have to be extracted [19]. On the other hand, microwave-assisted extraction was reported to be effective when used as a pretreatment to ultrasound-assisted extraction [26].…”
Section: Novel Technologies To Improve Enzymeassisted Hydrolysismentioning
confidence: 99%
“…The results showed that ultrasound microwave-assisted enzymatic hydrolysis (ultrasonic frequency of 40 kHz, microwave power of 10–800 W, temperature of 50 °C for 30–240 min) significantly increased the degree of hydrolysis of sweet potato protein hydrolysates and exhibited higher antioxidant activity compared with untreated samples . At present, ultrasound and microwave-assisted methods have also been successfully used to prepare active peptides from plants such as duckweed ( Lemna minor L. ), pineapple byproducts, and black soybeans, which have great application potential. ,, It is worth pointing out that the microwave-assisted method also has widespread application in solid-phase peptide synthesis. , …”
Section: Preparation Of Plant Protein-derived Active Peptidesmentioning
confidence: 99%
“…), protein hydrolysates, and bioactive proteolytic enzymes derived from pineapple (Salampessy et al, 2017;Montiel-Aguilar et al, 2020;Chakraborty et al, 2021). Bromelain, a protease enzyme, is abundant in the pineapple fruit pulp and its byproducts (Ketnawa et al, 2012;Mala et al, 2021a). In the food industry, it is used for meat tenderization, grain protein solubilization during the baking process, beer clarification, and as a supplement (Tochi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, bromelain is sensitive to extreme conditions such as high temperature, gastric proteases in stomach juice, high acidity, and organic solvents, and thus, reduces its functionalities and bioavailability (Xue et al, 2010;Mala et al, 2021a). Its instability under such stress conditions reduce its enzymatic activity, decrease its health benefits, and limit its pharmacological applications.…”
Section: Introductionmentioning
confidence: 99%